KICKING AND ITS BIOMECKANICAL CHARACTERISTICS IN RUGBY - P. Velkov (Trakia Journal of Sciences)
The study features a biomechanical analysis of kicking the ball in rugby. Although rugby has a long history, it is understudied in our country. When taking a place kick in the game, the ball should achieve its maximum speed. The skills of place kicking are unique because of the specific shape of the ball, the use of kicking tee, and the angles of the swing. Here we shall explore this proximal-distal sequence aka the combined speed principle with the outcome of reaching maximum ball speed, which requires maximum speed of the foot prior to the contact with the ball.